Long-term trends in the burden of cancer attributable to high body mass index in China from 1990 to 2021 - Zhouwei Zhan; Yi Zeng; Shaohua Xu; Hongju Chen; Rui Huang; Wei Lin; Jiami Yu; Xiaojie Wang; Chunkang Yang; Zengqing Guo; Bijuan Chen (Frontiers in Nutrition)
BackgroundHigh body mass index (BMI) is a well-established modifiable risk factor for multiple cancer types. However, the long-term trends and demographic patterns of total cancer burden attributable to high BMI in China have not been fully characterized. This study aimed to assess the magnitude, temporal trends, and demographic drivers of BMI-related cancer burden in China from 1990 to 2021.MethodsData on total cancer burden attributable to high BMI were obtained from the Global Burden of Disease Study 2021. Key indicators included deaths, disability-adjusted life years (DALYs), years lived with disability (YLDs), and years of life lost (YLLs). Age-standardized rates (ASRs) were estimated by sex and age group. Joinpoint regression and age-period-cohort (APC) analyses were performed to assess trends, and decomposition analysis was used to quantify the contributions of population growth, population aging, and epidemiological changes.ResultsIn 2021, high BMI accounted for 58,745 cancer deaths and 1.66 million DALYs in China. Compared with 1990, age-standardized death and DALY rates increased by approximately 1.7-fold and 1.6-fold, respectively. Males had higher age-standardized rates of deaths, DALYs, and YLLs, while females exhibited higher YLD rates. The burden peaked in the 50–69 age group and varied by sex across age strata. Colorectal, liver, kidney, and breast cancers were the largest contributors to the BMI-related cancer burden. APC analysis revealed growing burden across age and period dimensions, with higher DALY and mortality rates observed in more recent birth cohorts. Decomposition analysis showed that the increase in deaths was mainly driven by epidemiological change and population growth, while DALY increases were influenced by all three components, with a stronger impact in males.ConclusionThe burden of cancer attributable to high BMI in China has risen substantially over the past three decades, with clear sex, age, and cohort-specific differences. Comprehensive public health strategies targeting obesity prevention and cancer control are urgently needed.